The variability of competitive performance and pacing strategies in different rounds of the 400 m and 800 m freestyle swimming races at the 2017-2024 World Swimming Championships - Fang, J.; Li, Y.; Cheng, Y. (Frontiers in Sports and Active Living, 2024)
Introduction: This study aims to analyze the competitive performance and pacing strategies (PS) of medalists and non-medalists in different rounds of the 400 m and 800 m freestyle at the World Swimming Championships.